Preparing Polypropylene Auxetic Foam by a One‐Pot CO2 Foaming Process. Issue 3 (28th October 2021) - Li, Niexin; Liu, Ziqi; Shi, Xingbo; Fan, Donglei; Xing, Haiping; Qiu, Jian; Li, Minggang; Tang, Tao
Abstract : At present, the direct preparation of polymer foam with negative Poisson ratio (auxetic foam) from nonpolar polymer resins is still a challenge. Herein, a one‐pot CO2 foaming method is established to directly prepare closed‐cell auxetic foams with different cellular structures (bimodal cell structure and homogeneous cell structure) from polypropylene (PP) resin by introducing hydrophilic additives (NaCl) into PP and regulating foaming conditions. The effects of foaming temperature, saturation time, and size of added NaCl on Poisson's ratio are studied. The comparison with PP/talc composites shows that the presence of NaCl plays a crucial role in the formation of the negative Poisson ratio of foam. Furthermore, the regulation of the size of negative Poisson ratio is achieved by controlling the amount of NaCl in PP/NaCl composites. This study has important reference significance for the preparation of nonpolar polymer auxetic foams. Abstract : The polypropylene (PP)/NaCl composites absorb water during foaming process, which provides the driving force for forming the reentrant structure through a pressure difference between the inside and outside of the cell, originated from water vaporization during depressurizing and steam liquefaction after cooling.